Effect of Almond and Thyme Oils on the Nutritional Profile of Broiler and Quail Meat - Samar; Yasmeen, Roheela; Gillani, Syeda Shaista; Iqbal, Syeda Saira; Usman, Shumaila (International Health Review, 2023)
Broiler and quail farming have experienced significant growth in Pakistan. Broiler chickens are primarily raised for their meat, whereas quails are raised for both their meat and eggs. This study aims to assess the quality and shelf life of broiler and quail meat when treated with thyme and almond essential oils and stored under refrigeration at 4℃. Proximate analysis was conducted on the quail and broiler meat samples, assessing moisture, ash, protein, and fat content to evaluate their nutritional value. Nanoemulsions of thyme and almond oil were prepared at two different concentrations (15% and 25%) and applied to the meat samples, which were then divided into five groups: a control group and four treatment groups. The four treatment groups were labelled as 15% thyme, 25% thyme, 15% almond, and 25% almond. The meat samples were analyzed for their proximate composition (moisture, ash, protein, and fat) and pH levels on the first, seventh, and twenty-first days of the experiment. Fresh samples of chicken and quail meat exhibited significant differences in moisture, ash, proteins, and fats, while pH levels remained relatively stable. On the 7th and 21st days, there was an observable increase in ash, protein, and fat values across all experimental groups, while pH levels remained relatively unchanged. Broiler meat had the highest protein content, while quail meat contained the highest fat levels. Among the treatments, it was observed that thyme oil at a 25% concentration yielded the best results for preserving nutritional values close to their initial levels when compared to the other experimental groups. Based on the study's findings, it is reasonable to conclude that thyme oil, in comparison to almond oil, maybe a more effective option for preserving meat and extending the shelf life of stored meat.